2018
DOI: 10.1111/mve.12325
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the susceptibility of a European Aedes albopictus strain to dengue virus under a simulated Mediterranean temperature regime

Abstract: Dengue virus (DENV) has re-emerged in Europe driven by the geographic expansion of the mosquito species Aedes albopictus and Aedes aegypti (Diptera: Culicidae) and the introduction of the virus by viraemic travellers. In the present study, the vector competence (VC) of Ae. albopictus collected in Catalonia (northeast Spain) was evaluated for two different DENV strains, DENV-1 and DENV-2, the serotypes responsible for all outbreaks of dengue that have occurred in Europe. Mosquitoes were reared under environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…In fact, a recent study has experimentally shown that an Ae. albopictus strain from Catalonia could sustain DENV-2 replication under a simulated Mediterranean temperature regime [38], which would be in agreement with our detection of a high viral load in the DENV-positive mosquito pool in the summer 2015.…”
Section: Discussionsupporting
confidence: 89%
“…In fact, a recent study has experimentally shown that an Ae. albopictus strain from Catalonia could sustain DENV-2 replication under a simulated Mediterranean temperature regime [38], which would be in agreement with our detection of a high viral load in the DENV-positive mosquito pool in the summer 2015.…”
Section: Discussionsupporting
confidence: 89%
“…albopictus and Ae. aegypti (a recognized epidemic vector) showed similar TE rates for CHIKV [126,[147][148][149][150][151][152], DENV-1 [153][154][155][156][157], and DENV-2 [126,147,154,155,[157][158][159], but Ae. aegypti was more efficient at transmitting ZIKV [126,[160][161][162][163][164][165][166][167][168][169][170][171] and YFV [127,128,[172][173][174][175].…”
Section: Arbovirus Transmissionmentioning
confidence: 99%
“…The best way to estimate the risk of dengue fever outbreak is to measure whether mosquitoes are infected with dengue virus while simulating environmental conditions at mosquito collection sites [68]. In this study, we used a temperature and humidity recorder to record the hourly temperature and humidity of mosquitoes living in the field, and simulated the hourly temperature and humidity changes in the field environment in an artificial climate box, which was more detailed than the temperature fluctuation conditions set by Brustolin et al (daytime temperature 26 °C, nighttime temperature 22 °C [68]. In the present study, the temperature fluctuated from, the relative humidity fluctuated from 55.4 to 100%, and the average humidity was 84% in summer.…”
Section: Discussionmentioning
confidence: 99%